Serum hyaluronic acid predicts protein-energy malnutrition in chronic hepatitis C. Issue 24 (June 2016) - Nishikawa, Hiroki; Enomoto, Hirayuki; Yoh, Kazunori; Iwata, Yoshinori; Hasegawa, Kunihiro; Nakano, Chikage; Takata, Ryo; Kishino, Kyohei; Shimono, Yoshihiro; Sakai, Yoshiyuki; Nishimura, Takashi; Aizawa, Nobuhiro; et al.
Abstract : Abstract: Serum hyaluronic acid (HA) is a well-established marker of fibrosis in patients with chronic liver disease (CLD). However, the relationship between serum HA level and protein-energy malnutrition (PEM) in patients with CLD is an unknown. We aimed to examine the relationship between serum HA level and PEM in patients with chronic hepatitis C (CHC) compared with the relationships of other serum markers of fibrosis. A total of 298 CHC subjects were analyzed. We defined patients with serum albumin level of ⩽3.5 g/dL and nonprotein respiratory quotient <0.85 using indirect calorimetry as having PEM. We investigated the effect of serum HA level on the presence of PEM. Receiver operating characteristic curve (ROC) analysis was performed for calculating the area under the ROC (AUROC) for serum HA level, platelet count, aspartate aminotransferase (AST) to platelet ratio index, FIB-4 index, AST to alanine aminotransferase ratio, and Forns index for the presence of PEM. The median serum HA level in this study was 148.0 ng/mL (range: 9.0–6340.0 ng/mL). In terms of the degree of liver function (chronic hepatitis, Child-Pugh A, B, and C), the analyzed patients were well stratified according to serum HA level (overall significance, P  < 0.0001). The median value (range) of serum HA level in patients with PEM (n = 61) was 389.0 ng/mL (43.6–6340.0 ng/mL) and that in patients without PEM (n = 237) was 103.0 ng/mL (9.0–783.0 ng/mL) ( P  < 0.0001). Among 6 fibrosis markers, serum HA level yielded the highest AUROC with a level of 0.849 at an optimal cut-off value of 151.0 ng/mL (sensitivity 93.4%; specificity 62.0%; P  < 0.0001). In the multivariate analysis, serum HA level was found to be a significant prognostic factor related to the presence of PEM ( P = 0.0001). In conclusion, serum HA level can be a useful predictor of PEM in patients with CHC.